Ocular manifestation in Rheumatoid arthritis and Juvenile rheumatoid arthritis - Kumar, Prajjwal (Journal of Kathmandu Medical College, 2014)
Background: Rheumatoid arthritis (RA) and juvenile rheumatoid arthritis (JRA) are systemic autoimmune diseases characterized by synovitis and a wide range of extra articular manifestations. Ocular involvement occurs frequently in both diseases and it may affect all layers. Objectives: To identify different types of ocular involvement in cases of Adult Rheumatoid Arthritis (RA) and Juvenile Rheumatoid Arthritis (JRA) in a tertiary care hospital in Nepal and to compare the prevalence of those ocular findings among them. Methods: In this hospital based cross-sectional study, all cases referred from Orthopaedics department, Paediatrics department, Internal Medicine Rheumatology clinic of Kanti Children Hospital presenting to the OPD of BP Koirala Lions Centre for Ophthalmic Studies (BPKLCOS), cases admitted in eye ward and orthopaedics ward from 1st February 2009 to 31st July 2010 were included. Patients below 15 years of age were included in Juvenile Arthritis group. Detailed systemic and ocular history was taken as per the proforma and detailed ocular examination was carried out. Paired t-test was used as the statistical tool to find out the significant difference. Results: Among 50 cases included in the study the cases of Rheumatoid Arthritis were 32 (64%) and Juvenile Rheumatoid Arthritis were 18 (36%). In the study, females (32) were predominant as compared to males (18). In RA group females predominated whereas in JRA group males predominated. Among 50 cases of arthritis 33 cases showed ocular involvement (25 from RA group and seven from JRA group). Among them, the most common ocular manifestation was dry eye 22% (mild, moderate and severe forms) followed by uveitis nine percent, corneal ulcers two percent, viral keratitis two percent, conjunctivitis two percent, episcleritis one percent and glaucoma one percent. Conclusion: Cases of Rheumatoid Arthritis and Juvenile Rheumatoid Arthritis should be subjected to regular ocular evaluation because of possibility of ocular involvement due to disease itself or the medication being used to treat them. Ocular manifestations due to RA and JRA are not uncommon in our population thus early identification of the disease and their proper management would possibly prevent visual loss in the majority of the cases. DOI: http://dx.doi.org/10.3126/jkmc.v2i4.11775 Journal of Kathmandu Medical College Vol. 2, No. 4, Issue 6, Oct.-Dec., 2013 Page: 181-189